Pengaruh Media Pembelajaran Berbasis Smartphone Terhadap Pada Materi Gerak Lurus - Ida Sriyanti (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2021)
This study aims to determine the effect of smartphone-based learning media on student learning outcomes in straight motion material for class X. This research was conducted at SMA Negeri 22 Palembang in the odd semester of the 2019/2020 school year. The research method used was a quasi experimental research design with nonequivalent control group design. The research sample was determined using simple random sampling technique, the research sample used was class X IPA 1 as the experimental class and class X IPA 2 as the control class. The learning process in the experimental class uses smartphone-based learning media and the control class does not use smartphone-based learning media. This research instrument uses a test that meets the categories to measure student learning outcomes in the form of multiple choices. The statistical test results used were the normality test, homogeneity test, and hypothesis testing assisted by the IBM SPSS Statistics 22 program.The results of this study indicate that the average posttest score obtained by the experimental class students is 81.2 and the average posttest score obtained control class students 65. The output of the IBM SPSS Statistics 22 program on the Nonparametric test, namely the Kruskal-Wallis Test shows Sig <0.05 (0.000 <0.05), then H0 is rejected and Hα is accepted, so it can be concluded that there is an influence of learning media smartphone based on student learning outcomes.